VISOR: virtual machine images management service for cloud infarestructures - Pereira, João Daniel Raposo (2015)
Cloud Computing is a relatively novel paradigm that aims to fulfill the computing as utility dream. It has appeared to bring the possibility of providing computing resources (such as servers, storage and networks) as a service and on demand, making them accessible through common Internet protocols. Through cloud offers, users only need to pay for the amount of resources they need and for the time they use them. Virtualization is the clouds key technology, acting upon virtual machine images to deliver fully functional virtual machine instances. Therefore, virtual machine images play an important role in Cloud Computing and their efficient management becomes a key concern that should be carefully addressed. To tackle this requirement, most cloud offers provide their own image repository, where images are stored and retrieved from, in order to instantiate new virtual machines. However, the rise of Cloud Computing has brought new problems in managing large collections of images. Existing image repositories are not able to efficiently manage, store and catalogue virtual machine images from other clouds through the same centralized service repository. This becomes especially important when considering the management of multiple heterogeneous cloud offers. In fact, despite the hype around Cloud Computing, there are still existing barriers to its widespread adoption. Among them, clouds interoperability is one of the most notable issues. Interoperability limitations arise from the fact that current cloud offers provide proprietary interfaces, and their services are tied to their own requirements. Therefore, when dealing with multiple heterogeneous clouds, users face hard to manage integration and compatibility issues. The management and delivery of virtual machine images across different clouds is an example of such interoperability constraints. This dissertation presents VISOR, a cloud agnostic virtual machine images management service and repository. Our work towards VISOR aims to provide a service not designed to fit in a specific cloud offer but rather to overreach sharing and interoperability limitations among different clouds. With VISOR, the management of clouds interoperability can be seamlessly abstracted from the underlying procedures details. In this way, it aims to provide users with the ability to manage and expose virtual machine images across heterogeneous clouds, throughout the same generic and centralized repository and management service. VISOR is an open source software with a community-driven development process, thus it can be freely customized and further improved by everyone. The conducted tests to evaluate its performance and resources usage rate have shown VISOR as a stable and high performance service, even when compared with other services already in production. Lastly, placing clouds as the main target audience is not a limitation for other use cases. In fact, virtualization and virtual machine images are not exclusively linked to cloud environments. Therefore and given the service agnostic design concerns, it is possible to adapt it to other usage scenarios as well.